Studies in Indian economy Prof. P. N. Mathur memorial volume - Koti, Raghunath K. (ed); Venkatramaiah, P. (ed); Hasim, S. R. (ed); Koti, Raghunath K. (ed) (Mumbai Himalaya Publishing House, 1996)
Development planning